“Prostate telocytes change their phenotype in response to castration or testosterone replacement” - Felisbino, Sérgio Luis [UNESP] (2019)
Telocytes are CD34-positive cells with a fusiform cell body and long, thin cytoplasmic projections called telopodes. These cells were detected in the stroma of various organs, including the prostate. The prostate is a complex gland capable of undergoing involution due to low testosterone levels; and this condition can be reversed with testosterone replacement. Telocyte function in the mature prostate remains to be dermined, and it is not known whether telocytes can take place in tissue remodeling during prostate involution and regrowth. The present study employed structural, ultrastructural and immunohistochemical methods to investigate the telocyte’s phenotypes in the ventral prostate (VP) from control (CT), castrated (CS) and testosterone replacement (TR) groups of adult male Wistar rats. Telocytes were found in the subepithelial, perimuscular and interstitical regions around glandular acini. Telocytes from CT animals have condensed chromatin and long and thin telopodes. In CS group, telocytes appeared quiescent and exhibited layers of folded up telopodes. After TR, telocytes presented loose chromatin, abundant rough endoplasmic reticulum and enlarged telopodes, closely associated with bundles of collagen fibrils. We called these cells “telocytes with a synthetic phenotype”. As testosterone levels and glandular morphology returned toward to the CT group parameters, after 10 days of TR, these telocytes progressively switched to the normal phenotype. Our results demonstrate that telocytes exhibit phenotypic plasticity upon androgen manipulation and interact with fibroblast and smooth muscle cells to maintain glandular architecture in control animals and during tissue remodeling after hormonal manipulation.